Atomização a gás do aço ferramenta A2: efeito dos parâmetros de processo nas características do pó - Mathias, Laura Emi Tavoni (2022)
Gas atomization is the main method in powder metallurgy to produce powders for additive manufacturing (AM). The gas atomization process allows generally spherical and very fine metallic powders with great yield on the particle size range for AM applications. Moreover, this is a rapid solidification process that ensures chemical homogeneity and a high degree of microstructural refinement. Iron-based alloys have wide properties range and low cost, in which tool steels are especially important for industrial applications. This project produced A2 tool steel powders by gas atomization and evaluated the influence of the process parameters on the characteristics of the powders. No systematic study has been carried out on atomization and AM of this tool steel. Thus, analyzing the gas atomization process of this material is important to ensure the production of powders with proper characteristics. The statistical tool of design of experimental (DOE) was applied, and the atomization pressure and melt superheat process parameters were analyzed. The response variables analyzed were morphology, median particle size, particle size distribution, density and flowability. The powder characterization was done by laser diffraction, sieving, scanning electron microscopy, chemical analyses by EDS, flowability by Hall and Carney Flowmeter Funnel, density by helium pycnometry and apparent density. This study showed that the gas atomization process of the A2 tool steel was suitable for the production of powders for applications in AM. The model proposed by Lubanska, which formulate the mass median particle diameter, was also validated. Furthermore, the process with the lowest pressure level (20Bar) and the highest melt superheat (300K) has the lowest gas/metal ratio and mean particle size (D50) and particle size distribution similar to the other powders produced.